Training opportunities in higher education institutions : a case study of IIUM's administrative staff - Nor Amna Afiqah bt Mohammad Nor (Institute of Education, International Islamic University Malaysia, 2013)
The main purpose of this study is to explore the perceptions of the training programmes opportunities for administrative staff at the International Islamic University Malaysia, Gombak. This study uses a mixed methods design which includes both quantitative and qualitative approaches. In the first phase, the quantitative approach, a survey was conducted on 114 administrative staff to obtain data about the availability and usefulness of training programmes, and training impacts on knowledge and skills. Generally, the survey statistical data revealed that participants had positive perceptions about the training programmes opportunities offered by the IIUM. It was found that the mean classifications for training availability and usefulness, and the impacts of training on administrative staffs‟ knowledge and skills were considered high. Meanwhile, in the second phase, four semi-structured interviews were conducted to obtain more detailed, specific information based on the statistical tests. It represents a major aspect of data collection along with an investigation of the extent to which training programmes facilitate the attainment of the university‟s vision and mission and to understand the problems and dilemmas faced by the administrative staff. The major findings of both methods indicated that the training opportunities provided were very adequate and met the administrative staff‟s expectations. They were highly satisfied with the training convenience, training design, training content, training duration, and training methodology. Besides, the study showed that there is a positive increment in learning in terms of knowledge and skills. The data also revealed that the training programmes were significantly interrelated with the attainment of the university‟s vision and mission. Last but not least, there were several problems and dilemmas faced by administrative staff including the trainer, time constraint, irrelevant job scope and others. Thus, the problems that showed up